An overview on adverse drug reactions to traditional Chinese medicines. (19th May 2015) - Chan, Kelvin; Zhang, Hongwei; Lin, Zhi‐Xiu
<x xml:space="preserve">Abstract</x> The safe use of Chinese materia medica (CMM) and products in traditional Chinese medicine (TCM) practice conventionally relies on correct pharmacognostic identification, good agricultural and manufacturing practices based on pharmacopoeia standards and rational/correct CMM combinations with TCM‐guided clinical prescribing. These experience‐based principles may not absolutely ensure safety without careful toxicological investigations when compared with development of new pharmaceutical drugs. Clinically observed toxicity reports remain as guidance for gathering toxicological evidence, though essential as pharmacovigilance, but are considered as late events for ensuring safety. The overview focuses on the following factors: global development of TCM that has affected conventional healthcare; examples of key toxic substances in CMM; reported adverse drug reactions (ADRs) consequential to taking CMM and TCM products; and proposals on rational approaches to integrate the knowledge of biomedical science and the principles of TCM practice for detecting early ADRs if both TCM products and orthodox drugs are involved. It is envisaged that good control of the quality and standards of CMM and proprietary Chinese medicines can certainly reduce the incidence of ADRs in TCM practice when these medications are used.